PENGARUH HEDONIC SHOPPING MOTIVATION DAN SALES PROMOTION TERHADAP POSITIVE EMOTION SERTA DAMPAKNYA PADA IMPULSE BUYING - Indarni, Chindy Cherly; Susanta, Susanta; Hadi, Lukmono (Program Studi Ilmu Administrasi Bisnis, UPN Veteran Yogyakarta, 2020)
This research was conducted to determine the effect of Hedonic Shopping Motivation and Sales Promotion on Positive Emotion and its Impact on Impulse Buying. The sample size in this study was 69 respondents. The sampling technique used is Non Probability Sampling with purposive sampling for an infinite population. The data analysis technique used descriptive statistical analysis and inferential statistical analysis using the statistical method of Structural Equation Modeling using SmartPLS 3.0. The results of this study conclude that Hedonic Shopping Motivation has a significant effect on Positive Emotion, Sales Promotion has a significant effect on Positive Emotion, Hedonic Shopping Motivation has a significant effect on Impulse Buying, Sales Promotion has a significant effect on Impulse Buying, Positive Emotion has a significant effect on Impulse Buying. , Miniso Malioboro Mall Yogyakarta must pay attention to the stimuli used to increase sales. The way this is done is, among others, by providing stimuli that can make consumers feel happy with products, services, and sales promotions provided by Miniso so as to encourage consumers to do Impulse Buying while inside Miniso Malioboro Mall Yogyakarta.